Globalizing the boardroom among family-controlled listed companies on bursa Malaysia (an update) and Singapore – the effects of corporate governance on firm performance - Lee, Marissa Chen Li (2022)
The purpose of this research is to determine if corporate governance mechanism are more significant between Family-Controlled in Malaysia and Singapore. Corporate Governance mechanism that adopted in this research are number of board sizes (BS), percentage of independent directors (%ID), number of women directors (NOWD), number of foreign directors (NOFD), number of foreign qualifications (NOFQ), number foreign directors in audit committee (NOFDAC), and number of board meeting (NOBM). These mechanisms are applied to investigate its relationship towards firm performance. The firm performance is measured by return of assets (ROA), return on equity (ROE), and Tobin’s Q). The samples used in this research are 27 Malaysian Family-Controlled Companies and 13 Singaporean FamilyControlled Companies in the periods 2013-2020. This research applied Panel Data Analysis to investigate the overall 8 years results. There are 2 types of panel estimator approaches that can be implemented which are fixed effect and random effect. From previous research, there has significant relationship towards Malaysia Family-Controlled Companies which is on BS (ROA & ROE), as current research shows NOWD (ROA & ROE) and NOBM Tobin’s Q) have significant relationship with firm performance. While in Singapore, NOWD (ROA & Tobin’s Q), NOFD (Tobin’s Q), NOFDAC (ROA & ROE), and NOBM (ROA & ROE) have significant relationship towards Singapore Family-Controlled Companies.